POC CD4 Testing Improves Linkage to HIV Care and Timeliness of ART Initiation in a Public Health Approach: A Systematic Review and Meta-Analysis. - Lara Vojnov; Jessica Markby; Caroline Boeke; Lindsay Harris; Nathan Ford; Trevor Peter (PLoS ONE, 2016)
Background CD4 cell count is an important test in HIV programs for baseline risk assessment, monitoring of ART where viral load is not available, and, in many settings, antiretroviral therapy (ART) initiation decisions. However, access to CD4 testing is limited, in part due to the centralized conventional laboratory network. Point of care (POC) CD4 testing has the potential to address some of the challenges of centralized CD4 testing and delays in delivery of timely testing and ART initiation. We conducted a systematic review and meta-analysis to identify the extent to which POC improves linkages to HIV care and timeliness of ART initiation. Methods We searched two databases and four conference sites between January 2005 and April 2015 for studies reporting test turnaround times, proportion of results returned, and retention associated with the use of point-of-care CD4. Random effects models were used to estimate pooled risk ratios, pooled proportions, and 95% confidence intervals. Results We identified 30 eligible studies, most of which were completed in Africa. Test turnaround times were reduced with the use of POC CD4. The time from HIV diagnosis to CD4 test was reduced from 10.5 days with conventional laboratory-based testing to 0.1 days with POC CD4 testing. Retention along several steps of the treatment initiation cascade was significantly higher with POC CD4 testing, notably from HIV testing to CD4 testing, receipt of results, and pre-CD4 test retention (all p<0.001). Furthermore, retention between CD4 testing and ART initiation increased with POC CD4 testing compared to conventional laboratory-based testing (p = 0.01). We also carried out a non-systematic review of the literature observing that POC CD4 increased the projected life expectancy, was cost-effective, and acceptable. Conclusions POC CD4 technologies reduce the time and increase patient retention along the testing and treatment cascade compared to conventional laboratory-based testing. POC CD4 is, therefore, a useful tool to perform CD4 testing and expedite result delivery.